Comparative genetics of drought tolerance - Sorrells M.E.; Diab A.; Nachit M. (Durum wheat improvement in the Mediterranean region: New challenges, 2000)
This is a review of recent research on drought tolerance among grass species with a comparative genetics perspective. New technologies for evaluating, dissecting, and mapping components of drought tolerance as well as the transfer of this information among species is accelerating the understanding of this phenomenon. In addition, exploitation of the genetic variation and evolutionary advantages of certain species can enhance our knowledge and provide a source of genes for transfer to other species.
Seminar on Durum Wheat Improvement in the Mediterranean Region: New Challenges, 2000/04/12-14, Zaragoza (Spain)